ESTETIKA MAIN BUNGO DALAM PENYAJIAN GALOMBANG DUOBALEH DI NAGARI PITALAH KABUPATEN TANAH DATAR - Meri Susanti; Erlinda Erlinda; Andar Indra Sastra (Institut Seni Indonesia Padang Panjang, 2017)
ABSTRACT This research aims at revealing the concept of Main Bungo in Galombang Duo Baleh performance in Pitalah village, Tanah Datar district, West Sumatra. Main Bungo is an important aspect of the aesthetics of Galombang Duo Baleh presentation. The constituent elements of Main Bungo concept are movement quality, kiek (technique), raso (feeling), and movement presentation. While philosophical aspects contained in the concept of Main Bungo presentation are acting wisely based on magnanimity, the compactness of living in a group, and the beauty of body movement based on mancak movements. Main Bungo becomes the basic inspiration in Galombang Duo Baleh presentation in Pitalah village. The issue discussed in this article is related to the structural form of Galombang Duo Baleh presentation in Pitalah village, Tanah Datar district, West Sumatra. This research was based on qualitative data by using the methods of observation, interview, and documentation. Research results are: Main Bungo becomes the aesthetic orientation and the basic judgment of whether Galombang Duo Baleh presentation in Pitalah village is good or bad. Keywords: Main Bungo, Galombang Duo Baleh, Pitalah Village